The contemporary photography and its pictorial sharings: antinomies and convergences - Ribeiro, Niura Legramante (PORTO ARTE: Revista de Artes Visuais, 2017)
The sharing between photography and painting in contemporary art may present at least two founding regimes for the creation of works: to propose antinomies as discontinuities between the contents of image representation and to verbal narratives associated to it, seeking to tension them, or, on the other hand, to seek convergence between text and image. This articles aims to think about how the universe of pictorial tradition serves as a compositional framework for photographic practices, through the case study of particular works by Dirnei Prates and Felipe Cama.